Amongst sisters: rivals or equals? A study of The blind assassin, The other boleyn girl and Dust - Alexandra Lauren Correa Gabbard (2017)
This dissertation focuses on the conflicted interactions of sister characters in The Blind Assassin, by Margaret Atwood, The Other Boleyn Girl, by Philippa Gregory, and Dust, by Elizabeth Bear. The sisters form a special type of double, configured through gendered identities, transgressive acts of resistance and complex connections to mother figures. The analysis of the sister doubles relies on the theoretical support of feminist psychoanalysis and gender studies, with a focus on theories about body politics and ontological matricide. I propose a reconceptualization of the sisters conflicted relationship under the lens of sorority, portraying how the positive reconstruction of motherhood and maternity approximates the sisters and enables them to resist patriarchal control. This study reflects upon traditional psychoanalytical theories that view the double as a manifestation of estrangement and death, recasting the sisters doubling as a positive and empowering manifestation of their alterity and subjectivities. This work provides a reinterpretation of the sister pairs in the novels, analyzed under a feminist aegis, through the study of their struggles and the recognition of their acts of resistance, defiance and sorority.